Two different point G to A mutations in exon 10 of the porphobilinogen deaminase gene are responsible for acute intermittent porphyria. - Delfau, M H (1990)
Two mutations of the porphobilinogen (PBG) deaminase gene resulting in cross-reacting immunological material (CRIM) positive forms of acute intermittent porphyria (AIP) have been identified by in vitro amplification of cDNA and cloning of the amplified products in a bacterial expression vector. Both mutations resulted from G to A transitions in exon 10 of the gene and produced arginine to glutamine substitutions in the abnormal protein. Expression of mutant cDNA in Escherichia coli reveals that one but not the other of these amino acid changes results in a striking decrease of the optimal pH of the mutated enzyme. One or the other of these two mutations accounted for the defect causing AIP in six unrelated patients among the eight patients evaluated with the CRIM positive subtype of this disorder.